2013
DOI: 10.1177/0733464813510602
|View full text |Cite
|
Sign up to set email alerts
|

Religious Coping in Caregivers of Family Members With Dementia

Abstract: The degree of depression experienced by caregivers of individuals with dementia was examined in relation to religious coping strategies, religious practice, and spirituality in the framework of the stress and coping model. Caregivers of 191 persons with dementia completed the Religious Coping Scale, self-report measures of religious practices and spirituality, burden, and depression. There was no evidence that any religious coping strategy or religious practice moderated the relationship between caregiving str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 46 publications
1
13
0
4
Order By: Relevance
“…This qualitative study particularly underscores the powerful impact of religious coping methods, which is similar to previous quantitative studies with other religions [28,29]. This study also demonstrates primarily how Buddhism may influence the caregiving experience.…”
Section: Discussionsupporting
confidence: 81%
“…This qualitative study particularly underscores the powerful impact of religious coping methods, which is similar to previous quantitative studies with other religions [28,29]. This study also demonstrates primarily how Buddhism may influence the caregiving experience.…”
Section: Discussionsupporting
confidence: 81%
“…Certain other socioeconomic characteristics of the caregiver have been found to affect the caregiver's burden: gender : most primary caregivers are women because of the traditional female role to take care of older parents, and they reported greater feeling of burden than men [ 29 , 30 ], age : several studies found that advanced age of the primary caregiver was associated with a sense of burden [ 31 ] and other studies found younger primary caregivers reported more burden [ 32 ], education : whereas some studies reported that there is a connection between level of education and burden [ 29 ], others reported there is no such connection [ 33 ], and religiosity : some studies found that religious belief and religious rituals help to moderate the burden of the caregivers [ 34 ]. In contrast, coping strategies related to religiosity were not found to moderate the stress and depression of primary caregivers [ 35 ]. In addition, ethnic and cultural factors have been associated with caregivers' burden [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, researchers have looked at the relevance and positive outcomes related to church and worship attendance in persons living with dementia and caregivers. While the benefits of religiosity in families living with dementia have been well established Hodge, & Sun, 2012;Jing et al, 2016;Katsuno, 2003;Kevern, 2015;MacKinlay & Trevitt, 2010;Plunkett & Chen, 2015;Rathier, Davis, Papandonatos, Grover, & Tremont, 2015;Swinton, 2014)…”
Section: Religiosity For Persons Living With Dementiamentioning
confidence: 99%
“…In previous studies, researchers have looked at the relevance and positive outcomes related to church and worship attendance in persons living with dementia and caregivers. While the benefits of religiosity in families living with dementia have been well established (Epps et al, ; Hodge, & Sun, ; Jing et al, ; Katsuno, ; Kevern, ; MacKinlay & Trevitt, ; Plunkett & Chen, ; Rathier, Davis, Papandonatos, Grover, & Tremont, ; Swinton, ), no suggestions are given in recent studies for how to design or revise religious services in African American congregations to accommodate families living with dementia. Despite published literature on dementia‐friendly initiatives (Dementia Friendly America®, 2015), faith‐based activities and models are less prominent in the United States in comparison to the United Kingdom.…”
Section: Introductionmentioning
confidence: 99%